Bioremediation technologies for polluted seawater sampled after an oil-spill in Taranto Gulf (Italy): A comparison of biostimulation, bioaugmentation and use of a washing agent in microcosm studies. Issue 1 (15th May 2016) - Crisafi, F.; Genovese, M.; Smedile, F.; Russo, D.; Catalfamo, M.; Yakimov, M.; Giuliano, L.; Denaro, R.
Abstract: One of the main challenges of bioremediation is to define efficient protocols having a low environmental impact. We have investigated the effect of three treatments in oily-seawater after a real oil-spill occurred in the Gulf of Taranto (Italy). Biostimulation with inorganic nutrients allowed the biodegradation of the 73 ± 2.4% of hydrocarbons, bioaugmentation with a selected hydrocarbonoclastic consortium consisting of Alcanivorax borkumensis, Alcanivorax dieselolei, Marinobacter hydrocarbonoclasticus, Cycloclasticus sp. 78-ME and Thalassolituus oleivorans degraded 79 ± 3.2%, while the addition of nutrients and a washing agent has allowed the degradation of the 69 ± 2.6%. On the other hand, microbial community was severely affected by the addition of the washing agent and the same product seemed to inhibit the growth of the majority of strains composing the selected consortium at the tested concentration. The use of dispersant should be accurately evaluated also considering its effect on the principal actors of biodegradation. Highlights: Biostimulation treatments dominant signatures associated to hydrocarbonoclastic bacteria during the first 5 days. In the Bioaugmentation treatments hydrocarbonoclastic bacteria and α-proteobacteria were the dominant members. Washing agent induced a biodiversity profile different compared to the other treatments. The yield of the treatments as TPH degradation was slightly higher after the bioaugmentation test.